YouTube Video citing LIS research: : Thematic mapping and metric analysis based on YouTube interaction - Ibrahim, Cecep; Hamzah, Muthmainnah Aufaa; Fadhli, Rahmat (Record and Library Journal, 2025)
Background of the study: YouTube offers new opportunities for sharing Library and Information Science (LIS) research beyond traditional academic channels. Despite this potential, attention is limited regarding how LIS research circulates and engages audiences on this platform. Purpose: This study aims to map the thematic focus of YouTube videos that cite LIS research and to analyze their interaction metrics as indicators of audience engagement from an altmetrics perspective. Method: The study employed quantitative (descriptive and inferential statistics on YouTube interaction metrics) and qualitative (thematic analysis with inductive coding) methods on YouTube videos citing LIS research. Findings: Engagement was largely passive, with views dominating (97.41%). Dominant themes were: libraries as objects (36.47%), innovation/IT (32.44%), health information (25.34%), and social media (5.75%). The Vsauce video “The Zipf Mystery” demonstrated the potential to popularize LIS concepts like Zipf’s law. Conclusion: LIS research is increasingly cited on YouTube, confirming the platform’s potential as a complementary avenue for research dissemination and highlighting the growing convergence with digital public engagement. Future studies should focus on strategies to optimize YouTube as a scholarly communication tool.